Earnings Management versus Capital Structure: What Are the Chances of Companies Occurring Within the Discretionary Limit? - Lima, Samuel Lyncon Leandro de; Gomes, Adhmir Renan Voltolini; Souza, Roberto Francisco de; Dal Vesco, Delci Grapégia (Revista de Negócios, 2019)
The discussions about companies’ debts have been pertinent to researches for decades, but it is still a puzzle issue. The mainly aspect this issue is how managers chooses funding sources. In this sense, the purpose of this study is analyzing the chances of occurring companies within the discretionary limit in relation to their capital structure. This research was conducts by logistic regressions with a sample of 706 energy sector firms from 37 countries around the world, with financial data from the period 2015 to 2017, making the total of 2.118 observations. So, results shows that profitability, investment opportunities, firm size, low capital structure are variables that affect to the chances of companies occurring within the discretionary limit. These results evidenced that the discretionary limit can be greater than 1% of the return on asset (ROA). Based on this findings we suggest that for some sectors, the discretionary limit may be different from the energy sector. Besides this, it depends by the attention of the regulatory agents of each country, as well as the relevance of the companies sector to the others.